Neuroscience and criminal law: promises and limitations for the assessment of criminal responsibility - Γκότση (Georgia-Martha Gkotsi) Γεωργία-Μάρθα (Bioethica, 2016)
In recent years, an explosion of interest in neuroscience has led to the development of "Neuro-law," a new multidisciplinary field of knowledge whose aim is to examine the impact and role of neuroscientific findings in legal proceedings. Neuroscientific evidence is increasingly being used in US and European courts in criminal trials, as part of psychiatric testimony, nourishing the debate about the legal implications of brain research in psychiatric-legal settings. In this paper, we aim to examine the impact of Neuroscientific evidence in the assessment of criminal responsibility. We start with a brief historical survey of the relation between brain sciences and criminal law. We then present two criminal cases in the context of which neuroimaging techniques were introduced as evidence of diminished responsibility or irresponsibility and continue with a presentation of some significant limitations and difficulties that neuroscience faces in the assessment of penal responsibility. These limitations are scientific, legal but also of philosophical and conceptual nature. We conclude that addressing moral or legal responsibility might depend on scientific data, but requires entry to very different conceptual domains. The legal system cannot delegate to another field, scientific or otherwise, the ascription of legal meaning. Neuroscientific data, however accurate and reliable they may become in the future, cannot contribute to the assessment of criminal responsibility, unless they are contextualised and completed -or even confronted- with data collected on other levels of analysis, in particular on a psychological, anamnestic, sociological and economic level. Neurosciences, as sciences, can offer functioning and biological models of behaviours, while the assignment of responsibility is a normative issue. Although neuroscientific evidence can provide assistance in the evaluation of penal responsibility by introducing new determinisms in the behavioural analysis of offenders with mental disturbances, it does not dispense with the need to define the limits of responsibility and irresponsibility of the accused. This analysis, while it needs to take account of social, moral and political factors - in addition to elements contributed by experts - ultimately belongs to the legal sphere.